Cold acclimation increases cold tolerance independently of diapause programing in the bean bug, Riptortus pedestris - Rozsypal, J; Moos, M; Goto, S G (Bulletin of entomological research, 2018)
The bean bug (Riptortus pedestris) is a pest of soybeans and other legumes in Japan and other Asian countries. It enters a facultative adult diapause on exposure to short days. While photoperiodism and diapause are well understood in R. pedestris, knowledge of cold tolerance is very limited, as is information on the effect of diapause on cold tolerance. We examined the effect of photoperiod, cold acclimation, and feeding status on cold tolerance in R. pedestris. We found that cold acclimation significantly increased survival at -10°C in both long- and short-day adult R. pedestris. Since the difference in cold survival between long- and short-day cold-acclimated groups was only marginal, we conclude that entering diapause is not crucial for R. pedestris to successfully pass through cold acclimation and become cold tolerant. We observed similar effects in 5th instar nymphs, with both long- and short-day cold-acclimated groups surviving longer cold exposures compared with non-acclimated groups. Starvation, which was tested only in adult bugs, had only a negligible and negative impact on cold survival. Although cold tolerance significantly increased with cold acclimation in adult bugs, supercooling capacity unexpectedly decreased. Our results suggest that changes in supercooling capacity as well as in water content are unrelated to cold tolerance in R. pedestris. An analysis of metabolites revealed differences between the treatments, and while several metabolites markedly increased with cold acclimation, their concentrations were too low to have a significant effect on cold tolerance.
Keywords: metabolomika; cold tolerance; Acclimatization; diapause; Heteroptera; Diapause, Insect; Animals; cold acclimation; Metabolomics; nízká teplota; Cold Temperature; zvířata; Riptortus pedestris; aklimatizace; diapauza hmyzu